Systematic and Multidisciplinary Evaluation of Fibromuscular Dysplasia Patients Reveals High Prevalence of Previously Undetected Fibromuscular Dysplasia Lesions and Affects Clinical Decisions: The ARCADIA-POL Study. Issue 4 (April 2020) - Warchol-Celinska, Ewa; Prejbisz, Aleksander; Dobrowolski, Piotr; Klisiewicz, Anna; Kadziela, Jacek; Florczak, Elzbieta; Michalowska, Ilona; Jozwik-Plebanek, Katarzyna; Kabat, Marek; Kwiatek, Pawel; Nazarewski, Slawomir; Madej, Krzysztof; et al.
Abstract : Fibromuscular dysplasia (FMD), regarded as a generalized vascular disease, may affect all vascular beds and may result in arterial stenosis, occlusion, aneurysm, or dissection. It has been proposed to systematically evaluate all vascular beds in patients with FMD, regardless of initial FMD involvement. However, the impact of this approach on clinical decisions and on management is unknown. Within the prospective ARCADIA-POL study (Assessment of Renal and Cervical Artery Dysplasia–Poland), we evaluated 232 patients with FMD lesions confirmed in at least one vascular bed, out of 343 patients included in the registry. All patients underwent a detailed clinical evaluation including computed tomography angiography of intracranial and cervical arteries, as well as computed tomography angiography of the abdominal aorta, its branches, and upper and lower extremity arteries. In the study group, FMD lesions were most frequently found in renal arteries (87.5%). FMD was also found in cerebrovascular (24.6%), mesenteric (13.8%), and upper (3.0%) and lower extremity (9.9 %) arteries. Newly diagnosed FMD lesions were found in 34.1% of the patients, and previously undetected vascular complications were found in 25% of the patients. Among all FMD patients included in the study, one out of every 4 evaluated patients qualified for interventional treatment due to newly diagnosed FMD lesions or vascular complications. The ARCADIA-POL study shows for the first time that the systematic and multidisciplinary evaluation of patients with FMD based on a whole-body computed tomography angiography scan has an impact on their clinical management. This proved the necessity of the systematic evaluation of all vascular beds in patients with FMD, regardless of initial FMD involvement. Abstract : Supplemental Digital Content is available in the text.